Indigenous entomopathogenic nematodes from China for the biological control of Spodoptera litura (Lepidoptera: Noctuidae): a multistage evaluation - Jiale Xi; Tianyu Wu; Lei Liu; Yinuo Xu; Xiwen Lin; Xianqin Wei; Xiangde Yang; Weibin Ruan (Crop Protection, 2027)

CRISPR/Cas9-mediated miR-21 editing in high-grade urothelial carcinoma cells and its biological effects - Maria Carolina Yi Lin Lee; Juliana Alves Camargo; Giovana Caetano Vilas Boas; Karina Serafim Silva; Luana Pereira Silva; Carolina Mie Mioshi; Ruan Pimenta; Iran Amorim Silva; Katia Ramos Moreira Leite; William Carlos Nahas; Sabrina T dos Reis (Molecular Biology Reports, 2026)
Background Urothelial carcinoma, the predominant form of bladder cancer, represents a global public health challenge due to its high rates of recurrence and progression. At the molecular level, microRNA-21 (miR-21) has been characterized as an “oncomir” because of its ability to negatively regulate tumor suppressor genes, thereby promoting tumor survival and progression. In this context, the CRISPR/Cas9 system has emerged as a precise genome-editing tool. Objective To investigate the biological effects of miR-21 modulation using CRISPR/Cas9-mediated genome editing in the T24 high-grade invasive urothelial carcinoma cell line. Methods The CRISPR/Cas9 system was delivered as a ribonucleoprotein (RNP) complex. Editing efficiency was assessed using quantitative reverse transcription PCR (RT-qPCR). Functional effects were evaluated through gene expression assays, cell migration assays, as well as Matrigel invasion assays. The presence of the Cas9 protein was confirmed by immunofluorescence. Results CRISPR/Cas9 treatment targeting miR-21 showed a trend toward reduced miR-21 expression (p = 0.0563), although this did not reach statistical significance. A statistically significant increase in MASPIN (p < 0.0001) and PDCD4 (p = 0.0239), as well as a trend toward increased PTEN expression (p = 0.055), was observed following treatment. Functionally, a significant reduction in the migratory capacity of edited cells was observed after 48 h (p = 0.0334). The presence of Cas9 was successfully confirmed in transfected cells. Conclusion These findings suggest that CRISPR/Cas9-mediated modulation of miR-21 may influence tumor suppressor pathways and reduce the migratory potential of urothelial carcinoma cells.

Unveiling N-nitrosomorpholine precursors in wastewater using nontarget, target analysis and transformation mechanism - Jing Zhou; Bo Zhao; Jie Liu; Junhan Ruan; Li Lin; Yi Li (Environmental Pollution, 2026)

Mangiferin attenuates aflatoxin B1–Induced ferroptosis by activating of Nrf2-Signaling and mitochondrial biogenesis in human ovarian granulosa cells - Chi-Wai Ruan; Hsin-Yi Tsai; Chih-Hsin Hung; Ming-Wei Lin (Food and Chemical Toxicology, 2026)

OES-guided electrical and hydrodynamic control for efficient NOx synthesis in an advanced plasma-liquid bubble discharge reactor - Jianfei Guo; Leilei Dai; Michelle Zhou; Xiangyang Lin; Xukun Zhu; Yuxi Chen; Juer Liu; Yuting Li; Kirk Cobb; Nan Zhou; Roger Ruan (Chemical Engineering Journal, 2026)

ADAMTS7 selective inhibitor BAY-9835 alleviates acute myocardial infarction by suppressing the NF-κB-mediated pyroptosis - Yunzhi Ling; Yang Lyu; Hanchuan Chen; Biting Lin; Gengyu Zhou; Simiao Chen; Tingting Weng; Ziqing Ruan; Yuanfan Zhu; Zhaoju Zhu; Yansong Guo; Kaiyang Lin (Toxicology and Applied Pharmacology, 2026)

Electrolyte-enabled reversible ICl intercalation in graphite as transition metal-free cathodes - Zhaoheng Ruan; Hao Zhang; Huipeng Zeng; Baichuan Cui; Ruifan Lin; An Phan; Chun Hu; Jijian Xu (Science Bulletin, 2026)

Short-, medium-, and long-chain chlorinated paraffins in human serum from South China: Evidence of LCCP exposure and CP substitution - Weifeng Ruan; Jinling Peng; Xi He; Jiayi Song; Xiaozhen Zhang; Yuan Liu; Rongjie Shi; Lan Zhuo; Xiaoshi Lin; Guangshan Xie; Min Hu; Yousheng Jiang; et al. (Journal of Hazardous Materials, 2026)

Unveiling the role of soil in urban vegetation greenness: City-scale evidence from field sampling across green spaces in Shanghai - Hanxin Tang; Mengyao Ci; Quanbo Yu; Shuyi Zhang; Ruoxi Lin; Junjie Ruan; Qicheng Zhong; Min Liu (Journal of Cleaner Production, 2026)

Early microbial succession and matrix destabilization guide long-term preservation of refrigerated kelp - Neng-Pai Shi; Si-Chuang Tu; Bing-Bing Wu; Ru-Meng Xiao; Hai-Bin Pan; Sheng-Nan Lin; Roger Ruan; Xue-Mei Hou; Xiang-Yang Lin (Food Chemistry, 2026)

Management regimes underpin soil carbon accrual following forest conversion to tea plantations across China - Lin Chen; Li Ruan; Yu Duan; Biao Feng; Yixuan Bai; Scott X. Chang; Teng Yang; Yowhan Son; Yuwei Yuan; Shangwen Fu; Chuan Yue; Zhongyi Li; et al. (Science Bulletin, 2026)

Life cycle assessment of regionally functionally-zoned intensive pig farming systems: Carbon footprint analysis and mitigation strategies for sustainable production - Bing Wu; Zhiqi Wen; Zhepu Ruan; Xiaoxuan Lin; Yongjie Li; Zhuobiao Ni; Gengyuan Cai; Rongliang Qiu (Journal of Environmental Management, 2026)

Integrating environmental DNA and trawl surveys to assess seasonal dynamics of fish communities in the Oujiang River Estuary - Chen Weifeng; Ruan Huiting; Wang Wei; Xu Kaiping; Peng Xin; Zhu Rong; Lu Yumiao; Ye Shen; Lin Hungdu; Wang Chen; Zhou Xiaofeng (Frontiers in Marine Science, 2026)
Introduction Monitoring of estuarine fish biodiversity is often constrained by the inherent limitations of traditional survey methods and the complex, dynamic environmental conditions of estuarine habitats. Environmental DNA (eDNA) metabarcoding has emerged as a robust molecular tool for aquatic biodiversity assessment. Nevertheless, its complementary potential to conventional bottom trawling remains understudied in estuarine ecosystems. In this study, we integrated eDNA metabarcoding and bottom trawling to investigate the spatiotemporal dynamics of fish diversity in the Oujiang River Estuary (ORE). Methods Fish assemblage data were collected seasonally across four sampling periods at five fixed sites within the ORE. MiFish-U primers targeting the 12S rRNA gene were utilized for eDNA amplification. And twelve aquatic environmental variables were quantified to disentangle correlations between fish community structure and ambient environmental conditions. Multiple statistical approaches, including alpha diversity analysis, Principal Coordinate Analysis (PCoA) and PERMANOVA, were applied to quantify spatiotemporal shifts in fish assemblages, identify fish-environment correlations, and compare community discrepancies between the two survey methods. Results and discussion The combined approach detected a total of 100 fish species across 84 genera and 45 families. Specifically, eDNA metabarcoding identified 72 fish species, while bottom trawling captured 48 species, with only 20 species shared between the two methods. Fish assemblages exhibited distinct seasonal variations, with both survey methods revealing higher species richness during wet seasons. Temporal fluctuations in water temperature, dissolved oxygen, salinity and nutrient concentrations constituted the primary environmental drivers structuring estuarine fish assemblages, whereas spatial heterogeneity across sampling sites exerted no statistically significant influence on community composition. eDNA metabarcoding showed unique advantages in detecting pelagic, migratory, cryptic and endangered fish species, supporting effective biodiversity monitoring in topographically intricate estuarine waters. In contrast, bottom trawling provided reliable morphological identification and quantitative abundance data for demersal fish taxa, which helped resolve ambiguous species annotations derived from eDNA sequencing. In addition, seven IUCN-listed threatened fish species were documented during the field investigation. Collectively, our findings demonstrate that eDNA metabarcoding and bottom trawling serve as highly complementary, rather than mutually exclusive, tools for fish biodiversity assessment. The integration of the two methods enables a more comprehensive and accurate evaluation of estuarine fish diversity. This study validates the feasibility and efficacy of the combined monitoring framework for macrotidal estuaries and provides valuable scientific references for the ecological conservation and management of the Oujiang River Estuary as well as other similar coastal ecosystems.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Smoldering of crop residues emits a large amount of intermediate volatility organic compounds to the atmosphere - Hui Sun; Jinlong Wang; Wei Liu; Ling Ruan; Zhaomin Yang; Xueqi Ma; Xiaowen Chen; Li Xu; Lin Du; Qifan Liu; Kun Li (Journal of Hazardous Materials, 2026)

Climate variability, tree diversity and stand structure jointly regulate biomass carbon dynamics in two subtropical forest stands representing contrasting successional stages in eastern China - Lin Xu; Hongfeng Ruan; Mengping Tang; Yongjun Shi; Guomo Zhou (Agricultural and Forest Meteorology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Metal-modified nitrogen self-doped biochar as an electrode plate for electrocatalytic removal of methylene blue - Guanbiao Ruan; Yuehong Yang; Junya Wang; Gaoyuan Qin; Xiaoling Peng; Daozhao Lin (Journal of Environmental Management, 2026)

Multi-source data fusion empowered by machine learning enables accurate discrimination of Maotai-flavor Baijiu production techniques - Longyuan Lin; Ziying Ruan; Na Zhang; Yifeng Ye; Qianqian Zhang; Saige Wang; Jicheng Chen (Food Research International, 2026)

Dynamic cross-linked/conductive dual-network polyurethane for integrated EMI shielding, thermal management and motion sensing - Sijie Yu; Taotao Qiang; Xiaoyong Dong; Congcong Lin; Xiaonan Ruan; Guannan Dong; Haiyang Hu; Fangfang Dong; Chen Mi; Tianlin Chen; Chen Zhang; Longfang Ren (Chemical Engineering Journal, 2026)

Decoding microglial metabolic cell death and PANoptosis hub genes in subacute phase of traumatic brain injury: a multi-omics and experimental validation study - Zhe Wu; Bao-ya Yang; Jin-qing Lai; Shi-hong Lin; Long Lin; Jian-long Chen; Jia-xiang Pan; Yao-xin Ruan; Xiang-rong Chen (Apoptosis, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Long-term operational strategy of microalgal-bacterial granular sludge towards strengthened sulfadiazine antimicrobial resistance control - Shupeng Lin; Minmin Pan; Yanfang Ma; Zhihao Chen; Tao Lyu; Renjie Dong; Roger Ruan; Shan Liu (Journal of Hazardous Materials, 2026)

Engineering the cathode: Key to unlocking the potential of potassium-ion batteries - Yu Dong; Ning Wang; Wang-mi Chen; Qi Zhou; Ming-xiao Li; Zhen-tao Cui; Jia-qi Hou; Wen-lin Ruan; Bei-dou Xi (Chemical Engineering Journal, 2026)

Microalgae-mediated shaping of bacterial communities enhances antibiotic removal and antibiotic resistance control - Shupeng Lin; Minmin Pan; Yanfang Ma; Zhihao Chen; Tao Lyu; Renjie Dong; Roger Ruan; Shan Liu (Bioresource Technology, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Two new clerodane diterpenoids and their anti-inflammatory activity from Callicarpa integerrima - Muhammad Aurang Zeb; Xiao-Ying Ruan; Xing-Jie Zhang; Yu-Tong Xing; Meng-Ru Wang; Yuan-Lin Kong; Xiao-Li Li; Kai Jiang; Wei-Lie Xiao (Natural Product Research, 2026)

Pollutant control and material conversion of the waste graphite recovered from spent lithium-ion batteries: Preparation of building composite materials - Yusen Wu; Pengcheng Wang; Keyi Lin; Jiaqi Hu; Yonggao Fu; Jie Zhu; Jujun Ruan (Resources, Conservation and Recycling, 2026)

Hydrochemical insights into lithium enrichment mechanisms in Southern Tibet's geothermal systems - Jiexiang Li; Hankun Li; Chuanxia Ruan; Gideon Sagoe; Guanghui Tian; Shen Wang; Wenjing Lin (Journal of Geochemical Exploration, 2026)

Formation mechanism of high arsenic geothermal water in Gonghe basin, Northwest China - Zhen Wang; Yongge Li; Chuanxia Ruan; Fu Wang; Wenjing Lin; Yu Yang; Narsimha Adimalla (Journal of Geochemical Exploration, 2026)

Oxidative potential of PM2.5 in Guangzhou, Southern China: Source apportionment and association with airborne bacteria - Yuxin Huang; Senchao Lai; Baoling Liang; Jinpu Zhang; Chenglei Pei; Dachi Hong; Xiaoluan Lin; Zhaokang Ruan; Leitao Sun; Yingyi Zhang (Journal of Environmental Sciences, 2026)

Lack of adverse effects in a subchronic 90-day oral toxicity study of almond hull powder in Sprague-Dawley rats - Yuyang Yao; Juer Liu; Yanling Cheng; Qiming Miao; Xinyue Zhu; Jingyi Xie; Na Zhang; Wei Hua; Guangwei Huang; Xiangyang Lin; Shengquan Mi; Roger Ruan (Food and Chemical Toxicology, 2026)

Fe-Ce oxides modified γ-Al2O3 adsorbents for efficient capture of gaseous arsenic trioxide over a wide temperature range: The key role of oxygen vacancy for arsenic oxidation - Tianhao Lin; Licong Guan; Zesheng Ruan; Zhifeng Xu; Ruixiang Wang; Hui Liu; Zhilou Liu (Chemical Engineering Journal, 2026)

Associations of Iron Indicators with Cognitive Impairment Risk in Postmenopausal Women: Evidence from a Matched Case–Control Study and Back Propagation Neural Network Model - Wanting Chao; Peiyi Liu; Junyu Li; Yudan Hao; Huijun Zhou; Lijie Feng; Shasha Ruan; Xifei Yang; Jianjun Liu; Yankui Lin; Xian Wang (Molecular Neurobiology, 2026)

Boosting split-crRNA CRISPR/Cas12a activity by 3′-end extension of DNA activator for direct microRNA sensing - Lin Hou; Fangqi Ruan; Kairen Zhao; Baoxin Li (Analytica Chimica Acta, 2026)

Hydrocarbon generation and pore evolution in marine organic-rich shales across maturation stages - Xueying Wang; Kun Zhang; Zhenxue Jiang; Yanhua Lin; Yan Song; Chengzao Jia; Shu Jiang; Lin Jiang; Hulin Niu; Jing Li; Yunbo Zhang; Xingmeng Wang; et al. (Fuel, 2025)

AI-assisted SERS fingerprint of serum omics analysis for precision breast cancer screening - Lingna Wang; Weihua Hong; Jinyong Lin; Chengbin Fu; Yuanmei Chen; Zeyang Liu; Min Fan; Luyun Xu; Jianqing Ye; Chengtao Ruan; Chaobin Huang; Xueliang Lin; et al. (Chemical Engineering Journal, 2025)

Distinct Influence of Conventional and Biodegradable Microplastics on Soil Microorganisms and Nitrogen Cycling: Emphasizing the Effect of Biodegradable Polylactic Acid - Yuxin Ruan; Liangbin Lin; Yiyong Lin; Yanru Zhang; Jianfei Chen; Qingrong Qian (Water, Air, & Soil Pollution, 2025)

Quaternized fluorinated polyaryl ether anion exchange membranes with excellent dimensional stability for improved electrodialysis desalination - Huimin Ruan; Zhipeng Xu; Junyao Wang; Meng Wang; Zhihao Lin; Ning Ding; Daohui He; Jiangnan Shen (Desalination, 2025)

Paenibacillus wuxiensis sp. nov., a Novel Bacterium Capable of Producing Indole-3-Acetic Acid (IAA) and Inhibiting Rhizoctonia solani Kühn Isolated from Agricultural Soil - Cansheng Yuan; Luyao Ruan; Ying Yang; Lin Wang; Zhuang Ke; Jian He (Current Microbiology, 2025)

A neutral multivalent AIE–TICT scaffold: An off-on, wash-free fluorogenic strategy for biosensing glycan–protein interactions in live cells and mycobacteria - Huai-En Chang; Chien-Chin Chen; Yi-Jin You; Pei-Hsuan Lee; Bo-Chang Ruan; Hong-Luen Kwok; Ching-Tse Wu; Chuang-Rung Chang; Jiun-Han Chen; Eugene C. Lin; Pei-Jhen Li (Analytica Chimica Acta, 2025)

Construction of lithium single-ion polymer electrolytes with octuple hydrogen bonds: Realizing interface adaptation for all-solid-state lithium metal batteries - Tianwei Hao; Yujian Shen; Chaolong Yang; Mengqi Ma; Wenhong Ruan; MuSong Lin (Chemical Engineering Journal, 2025)

Integrative Analysis of the Microbiome and Metabolome of Broiler Intestine: Insights into the Mechanisms of Probiotic Action as an Antibiotic Substitute - Yang Li; Jian-Ling Zhang; Jia-Qi Chen; Zhuang Chen; Shi Liu; Jing Liu; Wen-Jie Huang; Jia-Zhou Li; Dong Ruan; Jun-Jin Deng; Zhi-Lin Wang (Probiotics and Antimicrobial Proteins, 2025)

An improved sample preparation method for strontium isotope stratigraphy: case study of early Miocene oysters and foraminifera from the Gulf of Suez, Egypt - Ting Ruan; Yue Cai; Qimei Guo; Nicholas Christie-Blick; Ahmed N. El-Barkooky; Abdel-Moneim El-Araby; Ahmed Zakaria; Zhengfan Lin; Chengcheng Wang; Raed Badr (Applied Geochemistry, 2025)

Decreasing sensitivity of human populations to temperature variability during 50–10 ka in China - Zinan Lin; Dan Zhu; Jiayi Zhou; Yuhan Gao; Zhen Wang; Eric Galbraith; Jiaoyang Ruan; Jiafu Zhang (Quaternary Science Reviews, 2025)

Occurrence and ecological risks of pharmaceuticals along the Yangtze River Basin of China: Insights from target analysis and suspect screening strategy - Chong Chen; Chengcheng Bu; Qi Wang; Yutong Zhang; Shaopeng Xu; Yu Hua; Ruolan Jia; Huiju Lin; Xiaolei Wang; Zhiwei Gan; Xiong Xiong; Limin Ma; et al. (Journal of Hazardous Materials, 2025)

Unprecedented triterpenes with anti-inflammatory activity from Limax maximus - Ya-feng Wang; Pei-de Tang; Rui-jie He; Zhang-bin Liu; Yong-qiong Wei; Jun Ruan; Bing-yuan Yang; Yong-lin Huang (Journal of Natural Medicines, 2025)

MLKL triggers NLRP3 activation in sodium arsenite-induced myocardial necroinflammation - Yixin Cui; Meng Zhang; Yi Xiao; Jinren Liu; Yonghui Chen; Xingran Ruan; Xu Zhao; Yinan Liu; Yawen Shi; Jing Tian; Lian Li; Xinhe Zhang; et al. (Toxicology, 2025)

Sustainable thermal conversion of waste wind turbine blades: Environmental impact and pollutant footprint analysis - Jinnuo Dai; Keyi Lin; Chenjie Zhu; Yusen Wu; Jujun Ruan (Environmental Impact Assessment Review, 2025)

Lactiplantibacillus plantarum GMNL-661 Ameliorates Clostridioides difficile Infection and Reconfigures Intestinal Microbiota in a Murine Model - Meng-Jia Li; Hong-Ming Chen; Yueh-Lin Chen; Yi-Hsin Lai; Cheng-Yu Lai; Jhen-Wei Ruan; Jenn-Wei Chen; Wan-Hua Tsai; Wen-Chien Ko; Pei-Jane Tsai (Probiotics and Antimicrobial Proteins, 2025)

The impact of season, temperature, and direct normal irradiance on IVF pregnancy outcomes: a retrospective cohort study - Chao Wang; Jiehua Chen; Zhong Lin; Li Shi; Qiuyan Ruan; Jiamin Long; Yanping Lao; Xiangli Niu (International Journal of Biometeorology, 2025)
Objective . This study assessed associations between season, temperature, direct normal irradiance (DNI), and clinical pregnancy outcomes in first fresh in vitro fertilization (IVF) cycle. Methods . We conducted a retrospective cohort study (June 2021-October 2023) of 1179 patients undergoing fresh IVF cycles. Inclusion criteria required age ≤ 45 years, first-time fresh embryo transfer cycles (long/antagonist protocol), excluding preimplantation genetic testing, frozen cycles, or incomplete data. Temperature and DNI were recorded from gonadotropin (Gn) initiation to oocyte retrieval. Binary logistic regression assessed seasonal impacts on clinical pregnancy, while restricted cubic splines (RCS) independently modeled temperature/DNI effects. Results . Compared to winter, clinical pregnancy likelihood was 1.74-fold higher in spring (95% CI:1.11–2.71, P = 0.015) and 1.53-fold in summer (95% CI:1.02–2.30, P = 0.042). Stratified analysis revealed a 2.02-fold increased likelihood in summer cycles using the long protocol (95% CI:1.07–3.82, P = 0.031), whereas no seasonal variation was observed in antagonist protocol. RCS regression analysis indicated a nonlinear relationship between temperature and clinical pregnancy outcomes, which was confirmed in the long protocol group. No significant correlations were observed with DNI or in patients treated with the antagonist protocol. Conclusions . Season and ambient temperature significantly impact IVF clinical pregnancy, especially in the long protocol, with the highest increase in pregnancy rates observed in summer, as well as within the 26.13℃ to 29.68℃ temperature range. No significant effects were observed with DNI or the antagonist protocol. These findings suggest that summer treatment may optimize IVF outcomes, but future studies should prioritize multi-center prospective designs with continuous temperature monitoring to define precise optimal ranges.

Fabrication of self-supporting hierarchical porous metallic glass for pH-universal hydrogen evolution reaction - Xingran Zhao; Junsheng Liu; Heting Zhang; Jihan Jiang; Jiaqing Lin; Jianan Fu; Yu Zhang; Xin Li; Wenqing Ruan; Jiang Ma (Chemical Engineering Journal, 2025)

Effects of DpWRI1-like gene overexpression in transgenic Dunaliella parva - Lingru Ruan; Juying Lin; Lina Wu; Yanyan Liang; Xiumin Zhang; Shiyu Liang; Limei Huang; Changhua Shang (Antonie van Leeuwenhoek, 2025)

Al3+ driven-hydrolysis of amide group presented in the interface between EVA and glass for the decapsulation of waste photovoltaic laminates - Yusen Wu; Jiahua Lu; Keyi Lin; Jujun Ruan (Resources, Conservation and Recycling, 2025)

Green collagen fiber-based organic-inorganic hybrid membrane material for the effective removal of p-arsanilic acid - Zhihong Zheng; Yi Lin; Zheyu Lin; Dacheng Zhang; Junhan Lin; Kailing Ruan; Chunxiang Lin; Xiaoxia Ye; Jie Chen (Journal of Environmental Chemical Engineering, 2025)

Selective interfacial polymerization improves reversibility of Si anodes - Wen Yang; Shuwei Li; You Liu; Yanyan Li; Ping Jiang; Xiaobo Hong; Gaofeng Li; Bo Fan; Fang Chen; Liangdong Lin; Zhijun Qiao; Dianbo Ruan (Chemical Engineering Journal, 2025)

Toxicity and Safety Assessment of Key Pesticides Used in Rice Fields on Rice Flower Carp (Procypris merus) - Qianxue Shao; Yongming Ruan; Ru Liang; Ruixin Jin; Zhixi Jin; Lin Xie; Yongqing Chi; Jiaojiao Xia; Pingyang Zhu (Fishes, 2025)
Integrated rice–fish farming, crucial for sustainable agriculture, relies on the judicious use of pesticide. This study evaluates the toxicity of six common rice-field pesticides on Procypris merus (rice flower carp), a key species in these systems. We conducted acute and chronic toxicity tests, assessing survival, growth, oxidative stress (SOD, CAT, MDA, 8-OHdG), and neurotoxicity (AChE). Results revealed a spectrum of toxicity: abamectin and trifloxystrobin were highly toxic; pretilachlor was moderately so; and glufosinate-ammonium, triflumezopyrim, and thiazole zinc were low. Notably, triflumezopyrim induced significant oxidative stress and DNA damage, while all three low-toxicity pesticides inhibited AChE activity, indicating potential neurotoxicity. Despite these effects, all observed toxicities were reversible within 7–14 days. Considering that the tested concentrations exceeded typical field application rates, glufosinate-ammonium, triflumezopyrim, and thiazole zinc are deemed relatively safe for P. merus at recommended dosages. Our findings provide critical insights for optimizing pesticide selection in rice–fish farming, balancing pest control with ecological safety, thereby informing sustainable agricultural practices.

Flexible CuInS2 nanosheet arrays for simultaneous realization of solar water evaporation and photothermal-enhanced photodegradation - Xingjian Zhang; Shukui Shi; Jiping Shi; Lu Ruan; Xin Li; Xiaoli Jin; Fengyun Su; Lin Guo; Haiquan Xie (Journal of Water Process Engineering, 2025)

Effects of herbicide mixtures on the diversity and composition of microbial community and nitrogen cycling function on agricultural soil: A field experiment in Northeast China - Qingyun Ma; Yiqing Zhou; Rebecca E. Parales; Siyu Jiao; Zhiyong Ruan; Lin Li (Environmental Pollution, 2025)

Improvement of analysis method for cable-reinforced ETFE cushion structure - Zhen Zhang; Xiongyan Li; Lin Ruan; Suduo Xue (Engineering Structures, 2025)

In search of nanofiltration membranes for efficient lithium extraction from carbonate-type salt lakes - Ren-Jie Fan; Chun-Xu Zhang; Fujun Xiong; Lin-Hui Niu; Xiang-Xuan Ruan; Xiaohu Wang; Zhen-Yuan Wang; Mei-Ling Liu; Shi-Peng Sun; Weihong Xing (Desalination, 2025)

Flexible self-decoupled pressure/proximity/temperature sensor for composite stimulus sensing with low signal crosstalk - Qi Hong; Junjie Qiu; Jianhong Hao; Zihan Lin; Ziyuan Zhou; Xishun Ruan; Tianxu Zhang; Fan Yao; Zhitong Wang; Zhaobin Li; Weiqiang Hong; Xianghui Li; et al. (Chemical Engineering Journal, 2025)

Dynamic whole genome amplification using digital microfluidics for single-cell sequencing - Qingyu Ruan; Changrui Shi; Xiaoye Lin; Weidong Ruan; Minghui Xu; Chaoyong Yang; Yukun Ren (Chemical Engineering Journal, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Transformation fate of bisphenol A in aerobic denitrifying cultures and its coercive mechanism on the nitrogen transformation pathway - Pei Hong; Yu Pang; Jing Xu; Qi Wang; Huiju Lin; Yuefei Ruan; Yilin Shu; Kai Zhang; Kenneth Mei Yee Leung (Environmental Research, 2025)

Negative regulation of hippo-mediated antiviral response targeted WSSV in Penaeus vannamei - Hong Shi; Wenyang Lin; Yibin He; Jie Ren; Yiwen Jian; Zhihao Huang; Caozhi Huang; Chenchen Zou; Lingwei Ruan (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

A review of the current status of nitrogen self-doped biochar applications - Guanbiao Ruan; Yuehong Yang; Xiaoling Peng; Junya Wang; Yongkang Guo; Weiyao Hu; Daozhao Lin (Journal of Environmental Chemical Engineering, 2025)

Three-dimensional Finite-Element Forward Modeling and Response Characteristic Analysis of Multifrequency Electromagnetic - Jun Zhou; Ke He; Zhi-yan Liu; Shuai Ruan; Hong-lin Ran (Applied Geophysics, 2025)

Harnessing metal-metal interactions for simultaneously boosting photocatalytic hydrogen and benzaldehyde production - Yajie Feng; Chi Lin; Yifei Huang; Bing Li; Yingxin He; Jiangping Ma; Chaogang Ban; Lujie Ruan; Hongxing Jia; Xiaoping Tao; Liyong Gan; Xiaoyuan Zhou (Chemical Engineering Journal, 2025)

DNAzyme assisted single amplification for FEN1 activity detection using a personal glucose meter - Mingxi Li; Weijie Zang; Shuiliang Wang; Zhannuo Lin; Shu Liu; Yiling Chen; Xiaohui Ruan; Yuanfang Luo; Chao Xing; Chunhua Lu (Analytica Chimica Acta, 2025)

A novel acid-free combined technology to achieve the full recovery of crystalline silicon photovoltaic waste - Mi Lin; Pengcheng Wang; Baojia Qin; Jujun Ruan (Waste Management, 2024)

In vitro and in vivo investigation of the inhibitory effects of Sinoporphyrin sodium-mediated Sonodynamic therapy on human oral squamous cell carcinoma - Guogang Dong; Limin Jia; Shuhua Gao; Monan Lin; Ruilin Wang; Fuyu Yang; Juanjuan Ruan; Yanhong Lv (Journal of Photochemistry and Photobiology B: Biology, 2024)

High-throughput prediction of stalk cellulose and hemicellulose content in maize using machine learning and Fourier transform infrared spectroscopy - Fanghui Chen; Xing Liu; Chengchen Lu; Mingxiu Ruan; Yujing Wen; Shaodong Wang; Youhong Song; Lin Li; Liang Zhou; Haiyang Jiang; Leiming Wu (Bioresource Technology, 2024)

Enhanced therapeutic potential of Flotillins-modified MenSCs by improve the survival, proliferation and migration - Fangfang Cheng; Longkai Ji; Pan Li; Zhisheng Han; Yanan He; Fen Yang; Zhihao Xu; Yonghai Li; Tao Ruan; Xinxing Zhu; Juntang Lin (Molecular Biology Reports, 2024)

The effect of paeoniflorin on the rewarding effect of methamphetamine and the associated cognitive impairment in mice - Xin-shuang Gong; Hai-xing Wang; Xiang-dong Yang; Zhao-ying Yu; Shu-jun Lin; Zhi-ting Zou; Jia-nan Lv; Li-yin Qian; Yu-er Ruan; Zi-zhen Si; Yi Zhou; Yu Liu (Metabolic Brain Disease, 2024)

From spent lithium-ion batteries to functional materials: A review - Tingjin Zhou; Keyi Lin; Yusen Wu; Baojia Qin; Jie Zhu; Zhe Huang; Zhenming Xu; Jujun Ruan (Resources, Conservation and Recycling, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Distribution pattern analysis of multiple antibiotics in the soil-rice system using a QuEChERS extraction method - Hui Jin; Jie Hou; Yuyu Ruan; Jiang Xu; Kun Yang; Daohui Lin (Science of The Total Environment, 2024)

Separation cathode materials from current collectors of spent lithium-ion battery through low-energy mechanical friction technology - Keyi Lin; Yusen Wu; Ying Shen; Yanrui Zheng; Zicheng Wang; Jinjuan Chen; Taoli Wu; Jie Zhu; Zhe Huang; Baojia Qin; Jujun Ruan (Resources, Conservation and Recycling, 2024)

Strategic small molecule engineering: Unleashing the full potential of Kevlar aramid membrane in organic solvent nanofiltration - Yanqing Xu; Jiaqi Xiong; Qite Qiu; Chenfei Lin; Junbin Liao; Huiming Ruan; Jiangnan Shen (Chemical Engineering Journal, 2024)

Pod canopy staggered-layer cultivation increases rapeseed (Brassica napus L.) yield by improving population canopy structure and fully utilizing light-energy resources - Gang Lin; Hongjiang Li; Zhonglong Yang; Ying Ruan; Chunlin Liu (European Journal of Agronomy, 2024)

Tessaracoccus lacteus sp. nov., Isolated from the Sludge of a Wastewater Treatment Plant - Jialin Tan; Kaiqing Yang; Gengbo Jiang; Zhuobiao Ni; Qingqi Lin; Zhepu Ruan; Rongliang Qiu (Current Microbiology, 2024)

Norditerpenoid alkaloids from Aconitum refractum var. circinatum as autophagy inducers - Mei-Zhen Ye; Zhen-Ling Wan; Hong-Yu Ruan; Yu-Qi Yang; Ying Chen; Lin Chen; Shuai Huang; Xian-Li Zhou (Phytochemistry, 2024)

Effects of luteolin supplementation on growth, histology, antioxidant capacity, non−specific immunity and intestinal microbiota of the red swamp crayfish (Procambarus clarkii) - Yanbin Lin; Shengxuan Li; Yulong Li; Liu Fang; Heng Zhang; Qian Wang; Guoliang Ruan (Animal Feed Science and Technology, 2024)

Description and Genomic Characteristics of Diaphorobacter limosus sp. nov., Isolated from a Sewage-Treatment Plant - Kaiqing Yang; Jialin Tan; Gengbo Jiang; Zhuobiao Ni; Qingqi Lin; Yuanqing Chao; Zhepu Ruan; Rongliang Qiu (Current Microbiology, 2024)

The study on the shortcut approach for cooperative disposal of arsenic-rich copper dust and waste acid to prepare high-purity copper - Feng Yan; Hongkun Dai; Yu Wang; Maoguang Ruan; Shanrong Zhao; Xiaohua Yu; Yan Lin (Journal of Cleaner Production, 2024)

Modified nano zero-valent iron coupling microorganisms to degrade BDE-209: Degradation pathways and microbial responses - Jing Ma; Yingping Li; Xing Zhang; Jingjing Li; Qingqi Lin; Yanping Zhu; Zhepu Ruan; Zhuobiao Ni; Rongliang Qiu (Journal of Hazardous Materials, 2024)

p-Toluenesulfonic acid enhanced neutral deep eutectic solvent pretreatment of soybean straw for efficient lignin removal and enzymatic hydrolysis - Wenxuan Wu; Peiwen Zhu; Liping Luo; Hongyan Lin; Yuheng Tao; Lingyu Ruan; Liqun Wang; Qing Qing (Bioresource Technology, 2024)

Experimental study on the mechanical behavior of segmental joints of shield tunnels strengthened by a steel plate-UHPC composite - Ren-Peng Chen; Bin-Yong Gao; Shi-Qiang Ruan; Huai-Na Wu; Meng Fan; Dong-Lin Feng (Tunnelling and Underground Space Technology, 2024)

Potential causal links and mediation pathway between urban greenness and lung cancer mortality: Result from a large cohort (2009 to 2020) - Wenjing Wu; Gonghua Wu; Jing Wei; Wayne R Lawrence; Xinlei Deng; Yuqin Zhang; Shirui Chen; Ying Wang; Xiao Lin; Dan Chen; Xinling Ruan; Qiaoxuan Lin; et al. (Sustainable Cities and Society, 2024)

Chaepseubakerins A–J, ten undescribed cytotoxic [11]-chaetoglobosins from an endophytic fungus Pseudeurotium bakeri - Fangfang Duan; Xiaogang Peng; Lin Liu; Xianggao Meng; An Jin; Hanli Ruan (Phytochemistry, 2024)

A clean process for liquid-phase synthesis of α-PbO based on the selective leaching of lead sulfate from spent lead paste - Zhangqing Chen; Kui Huang; Guoliang Huang; Xinke Shan; Lin Wei; Haili Dong; Jujun Ruan (Journal of Environmental Chemical Engineering, 2024)

Association of systemic inflammation with the obesity paradox in cancer: results from multi-cohort studies - Hailun Xie; Lishuang Wei; Heyang Zhang; Guotian Ruan; Xiaoyue Liu; Shiqi Lin; Jinyu Shi; Chenan Liu; Xin Zheng; Yue Chen; Hanping Shi (Inflammation Research, 2024)

Positive impacts of dietary prebiotic inulin on growth performance, antioxidant capacity, immunity, and intestinal microbiota of red swamp crayfish (Procambarus clarkii) - Qian Wang; Yanbin Lin; Heng Zhang; Wenhao Fan; Shengxuan Li; Guoliang Ruan; Liu Fang (Aquaculture International, 2024)

Genetic Diversity and Population Structure of Chinese Longsnout Catfish (Leiocassis longirostris) Using Microsatellite DNA Markers - Yanling Hou; Huan Ye; Xinhua Song; Jiahui Fan; Junyi Li; Jian Shao; Yizhou Wang; Danqing Lin; Huamei Yue; Rui Ruan; Chuangju Li (Fishes, 2024)
The Chinese longsnout catfish (Leiocassis longirostris) is an economically important freshwater fish in China; however, its wild resources have declined dramatically in recent decades. Understanding the genetic structure of Chinese longsnout catfish populations is crucial to guide breeding programs and fishy restoration. In this study, 15 highly polymorphic microsatellite DNA loci were used to evaluate its genetic diversity and population structure. Chinese longsnout catfish populations show high genetic diversity; they do not show significant genetic differentiation or systematic geographic pattern of variation. From the upper to the lower reaches of the Yangtze River, the genetic diversity of Chinese longsnout catfish populations showed an increasing trend. The Gezhouba and Three Gorges dams, which physically divide the Yangtze River into upstream and mid-downstream sections, did not contribute to the genetic differentiation of Chinese longsnout catfish populations. Hence, the source of broodstock is not critical for within-river breeding programs and stock enhancement to restore the wild population. In addition, possible effects of dams on differentiation among populations are crucial and long-term evaluation is essential.

Phosphorylation regulation of Lv-β-catenin of Litopenaeus vannamei by an immediate early protein WSV083 to reduce cell adhesion - Wenhao Wu; Chenchen Zou; Hong Shi; Chuanqi Wang; Wenyang Lin; Yueling Zhang; Yibin He; Lingwei Ruan (Aquaculture, 2024)

Particle size-dependent and route-specific exposure to liquid crystal monomers in indoor air: Implications for human health risk estimations - Huiju Lin; Xinxing Li; Xian Qin; Yaru Cao; Yuefei Ruan; Michael K.H. Leung; Kenneth M.Y. Leung; Paul K.S. Lam; Yuhe He (Science of The Total Environment, 2024)

Estimation of the riverine input of organic ultraviolet filters (OUVFs) from the Pearl River Estuary to the South China Sea during the early Covid-19 pandemic - Jiaji Sun; Huiju Lin; Yichun Lu; Yuefei Ruan; Jason C.H. Lam; Paul K.S. Lam; Tieyu Wang; Jong Seong Khim; Yuhe He (Science of The Total Environment, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Disruption of sex steroid hormones biosynthesis by short-term enrofloxacin antibiotic exposure in Carassius auratus var. Pengze - Jiming Ruan; Gen Wan; Zhen Lin; Jianzhen Huang; Xiaochen Tang; Huazhong Liu (Chemosphere, 2023)

An integrated mycotoxin-mitigating agent can effectively mitigate the combined toxicity of AFB1, DON and OTA on the production performance, liver and oviduct health in broiler breeder hens - Meng-Ling Ruan; Jie Wang; Zhi-Yuan Xia; Xue-Wu Li; Bo Zhang; Guan-Lin Wang; Yuan-Yuan Wu; Yanming Han; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Microbial community structure and its driving mechanisms in the Hangbu estuary of Chaohu Lake under different sedimentary areas - Yang Chen; Yaofei Xu; Yunmei Ma; Jie Lin; Aidong Ruan (Environmental Research, 2023)

Soil salinization increases the stability of fungal not bacterial communities in the Taklamakan desert - Litao Lin; Zhiyong Ruan; Xin Jing; Yugang Wang; Wenting Feng (Soil Ecology Letters, 2023)

Correction to: Estrogen receptor alpha mediates 17β-estradiol, up-regulates autophagy and alleviates hydrogen peroxide-induced vascular senescence - Xiuting Xiang; LiangZhen Xie; Jieqi Lin; Rahmawati Pare; Guanshen Huang; Jianming Huang; Yuyan Wang; Shicong Song; Yunjun Ruan (Biogerontology, 2023)

Enhanced Au bioleaching from waste central processing unit (CPU) slots in a bioreactor with 10 mA direct current - Chenxi Pang; Mi Lin; Yusen Wu; Jujun Ruan (Resources, Conservation and Recycling, 2023)

Reassessing the classification of Chang'e-5 basalts using pyroxene composition - Heng-Ci Tian; Wei Yang; Yubing Gao; Qing Zhou; Renhao Ruan; Yangting Lin; Xianhua Li; Fuyuan Wu (Lithos, 2023)

Black soldier fly pulp in the diet of golden pompano: Effect on growth performance, liver antioxidant and intestinal health - Zuzhe Li; Chengzong Han; Zhanzhan Wang; Zhenyu Li; Leshan Ruan; Heizhao Lin; Chuanpeng Zhou (Fish & Shellfish Immunology, 2023)

Exposure to three herbicide mixtures influenced maize root-associated microbial community structure, function and the network complexity - Qingyun Ma; Qingqing Li; Jie Wang; Rebecca E. Parales; Lin Li; Zhiyong Ruan (Environmental Pollution, 2023)

Mineralogical evidence of water activity in the northern lowlands of Mars based on inflight-calibrated spectra from the Zhurong rover - Honglei Lin; Yangting Lin; Yong Wei; Sheng Gou; Chi Zhang; Renhao Ruan; Yongxin Pan (Science China Earth Sciences, 2023)

The Effect of Water Spinach on the Water Quality, Antioxidant System, Non-Specific Immune Response, Growth Performance, and Carbon Balance in Red Tilapia Production - Yuan-Yuan Luo; Xian-Can Chen; Rui-Lin Xie; Zhuo-Hao Ruan; Zhi-Qiang Lu; Liang-Sen Jiang; Yi-Fu Li; Wen-Sheng Liu (Fishes, 2023)
In this study, the compound aquaculture model of red tilapia (O. mossambicus albina × O. urolepis hornorum) and water spinach (Ipomoea aquatica) was used to investigate the effect of water spinach rafts on the water quality, antioxidant system, non-specific immune response, and growth performance of red tilapia and the carbon balance of payments. Red tilapia is characterized by its high adaptability to different production environments and food sources, as one of the most productive fish in aquaculture, and is well accepted in the market due to its nutritional and organoleptic characteristics. The experiment lasted for nine weeks and included two systems: the red tilapia-water spinach raft aquaponics (AP) system with 10% cover ratio with water spinach floating beds, and the aquatic monoculture (AM) system with only red tilapia. The total phosphorus (TP), total nitrogen (TN), and nitrate nitrogen (NO−3-N) in the AM were higher than those in AP from the fifth to ninth week. On the second, third, fifth, and sixth weeks, the ammonia nitrogen (NH4+-N), in the AM was higher than those in the AP. From the seventh week, the pH of the AM was significantly lower than the AP, while the nitrite nitrogen (NO−2-N) was significantly higher than the AP. The water quality index of the AP was better than that of the AM, indicating that water spinach can remove the nutrients from aquaculture water bodies. The average daily gain and specific growth rate (SGR) of fish in AP were higher than those in the AM. The acid phosphatase (ACP), alkaline phosphatase (AKP), and catalase (CAT) activities in the hepatopancreas of red tilapia in the AP were also significantly higher than those in the AM, while the malondialdehyde (MDA) in the AP was lower than the AM. The serum ACP and CAT of red tilapia in the AP were also higher than those in the AM, while the MDA of fish in the AP was lower than the AM. The results showed that both the experimental group and the control group were carbon sources and released greenhouse gases into the atmosphere, but the total carbon emissions of the red tilapia and the water spinach symbiotic system in the experimental group was significantly lower than that of the control group (p

Catalytic fast co-pyrolysis of Douglas Fir and low-density polyethylene with nanocellulose-derived carbon catalyst for enhancing selectivity of hydrogen in syngas and mono-aromatic hydrocarbon in bio-oil products - Rongge Zou; Chenxi Wang; Moriko Qian; Ryan Lei; Yunfeng Zhao; Qingfa Zhang; Erguang Huo; Xiao Kong; Xiaona Lin; Lu Wang; Xuesong Zhang; Austin Gluth; et al. (Chemical Engineering Journal, 2023)

Estrogen receptor alpha mediates 17β-estradiol, up-regulates autophagy and alleviates hydrogen peroxide-induced vascular senescence - Xiuting Xiang; LiangZhen Xie; Jieqi Lin; Rahmawati Pare; Guanshen Huang; Jianming Huang; Yuyan Wang; Shicong Song; Yunjun Ruan (Biogerontology, 2023)

Newcastle disease virus nucleocapsid protein mediates the degradation of 14–3–3ε to antagonize the interferon response and promote viral replication - Qiufan Xu; Jianpeng Liang; Jiaqi Jin; Wanyan Wu; Jinlian Ren; Jiayu Ruan; Lei Fan; Weifeng Yuan; Juncheng Cai; Qiuyan Lin; Bin Xiang; Chan Ding; et al. (Veterinary Microbiology, 2023)

Mitigating the adverse effects of Aflatoxin B1 in LMH, IPEC-J2 and 3D4/21 cells by a novel integrated agent - Yi-Xin Mo; Meng-Ling Ruan; Jie Wang; Ying Liu; Yuan-Yuan Wu; Guan-Lin Wang; Yan-Ming Han; Hai-Feng Wan; Dessalegn Lamesgen; Kamil Kuča; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

The response mechanism of microorganisms to the organic carbon-driven formation of black and odorous water - Zhipeng Wei; Yaofei Xu; Yingying Shi; Xiaotian Zhou; Jie Lin; Aidong Ruan (Environmental Research, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Distribution Characteristics and Influencing Factors of Bio-elements in the Human Hair of Uyghur Communities in an Oasis Area of Xinjiang, China - Muyesaier Tudi; Fengqing Jiang; Li Wang; Hairong Li; Shuangmei Tong; Jiangping Yu; Min Meng; Lin sheng Yang; Muhammad Ubaid Ali; Qiming Jimmy Yu; Huada Daniel Ruan (Biological Trace Element Research, 2023)

Smart healthcare sensor with dual autonomous self-healing, repeatable skin adhesion/detachment, and hydrophilic/hydrophobic Janus surface for aquatic ambulatory electrophysiological monitoring - Ziyi Wang; Renjie Ruan; Genhui Lin; Shaohua He; Yanyun Liu; Chenchi Gong; Peijie Xiao; Jingyi Chen; Yi Lu; Yang Cao; Xiaocheng Lin; Jin Zhang (Chemical Engineering Journal, 2023)

Grain size distribution drives microbial communities vertically assemble in nascent lake sediments - Jie Lin; Xiaotian Zhou; Xiang Lu; Yaofei Xu; Zhipeng Wei; Aidong Ruan (Environmental Research, 2023)

Effects of landscape modification on coastal sediment nitrogen availability, microbial functional gene abundances and N2O production potential across the tropical-subtropical gradient - Ping Yang; Kam W. Tang; Linhai Zhang; Xiao Lin; Hong Yang; Chuan Tong; Yan Hong; Lishan Tan; Derrick Y.F. Lai; Yalan Tian; Wanyi Zhu; Manjing Ruan; et al. (Environmental Research, 2023)

Toxicologic effect of short-term enrofloxacin exposure on brain of Carassius auratus var. Pengze - Zhen Lin; Gen Wan; Jiayi Wu; Huazhong Liu; Fan Zhang; Xiaochen Tang; Jiming Ruan (Science of The Total Environment, 2023)

Recovery of pure lead and preparation of nano-copper from waste glass diodes via a clean and efficient technology of step-by-step vacuum evaporation-condensation - Taiyu Huang; Keyi Lin; Xiao Tan; Jujun Ruan (Resources, Conservation and Recycling, 2023)

Feasibility study on preparing economical and environmentally-friendly high-flowability ultra-high performance cementitious composites with original graded stone powder free recycled manufactured sands - Rui Ma; Lifeng Zhang; Yufeng Song; Gaohang Lin; Xiaoqian Qian; Kuangliang Qian; Shaoqin Ruan (Journal of Cleaner Production, 2023)

Effect of ventilation parameters on dust pollution characteristic of drilling operation in a metro tunnel - Zhuwei Xie; Chao Ruan; Zhongtai Zhao; Chen Huang; Yimin Xiao; Qian Zhao; Jianquan Lin (Tunnelling and Underground Space Technology, 2023)

Characterization of a new chlorimuron-ethyl-degrading strain Cedecea sp. LAM2020 and biodegradation pathway revealed by multiomics analysis - Qingyun Ma; Xiaoyan Han; Jinlong Song; Jie Wang; Qingqing Li; Rebecca E. Parales; Lin Li; Zhiyong Ruan (Journal of Hazardous Materials, 2023)

A green and designable natural deep eutectic solvent-based supramolecular solvents system: Efficient extraction and enrichment for phytochemicals - Zi-Hui Cai; Jian-Dong Wang; Lin Liu; Liu-Ding Ruan; Qi Gu; Xin-Yu Yan; Li-Na Fu; Peng-Quan Zhao; Su Zhang; Yu-Jie Fu (Chemical Engineering Journal, 2023)

Identification of a TEAD homolog from Litopenaeus vannamei in response to WSSV infection - Yiwen Jian; Lingwei Ruan; Wenyang Lin; Jie Ren; Yalin Yang; Hong Shi (Aquaculture, 2023)

Formation pathways, gas-solid partitioning, and reaction kinetics of PCDD/Fs associated with baghouse filters operated at high temperatures: A case study - Xiaoqing Lin; Xiaoxiao Wang; Yuxuan Ying; Angjian Wu; Zhiliang Chen; Lei Wang; Hong Yu; Hao Zhang; Aizhong Ruan; Xiaodong Li; Jianhua Yan (Science of The Total Environment, 2023)

Regulation mechanism of cyanide production and conversion of Pseudomonas fluorescens commonly used in bio-cyanidation of precious metals from waste printed circuit boards - Mi Lin; Zichun Yao; Pengcheng Wang; Yonggao Fu; Jujun Ruan (Resources, Conservation and Recycling, 2023)

Simultaneous detection of two herbicides in fruits and vegetables with nanoparticle-linked immunosorbent and lateral flow immunoassays - Eunice Y. Kwon; Xiaofan Ruan; Fei Yu; Yuehe Lin; Dan Du; Bernard J. Van Wie (Food Chemistry, 2023)

Remote sensing identification of green plastic cover in urban built-up areas - Wenkai Guo; Guoxing Yang; Guangchao Li; Lin Ruan; Kun Liu; Qirong Li (Environmental Science and Pollution Research, 2022)

Size-specific particulate matter and outpatient visits for allergic conjunctivitis in children: a time-stratified case-crossover study in Guangzhou, China - Jin Zhou; Lijun Fan; Hualiang Lin; Dehui Zheng; Lihong Yang; Dan Zhuo; Jiayang Zhuoma; Huan Li; Shiyu Zhang; Zengliang Ruan (Environmental Science and Pollution Research, 2022)

First report of leaf blight on Panax notoginseng caused by Pestalotiopsis trachycarpicola in China - Cheng Zhong Lan; Xiong Lin; Yu Li Dai; Lin Gan; Xiao Fei Liu; Hong Chun Ruan; Xiu Juan Yang (Journal of Plant Pathology, 2022)

Comprehensive comparison of the prognostic value of systemic inflammation biomarkers for cancer cachexia: a multicenter prospective study - Hailun Xie; Guotian Ruan; Lishuang Wei; Heyang Zhang; Yizhong Ge; Qi Zhang; Shiqi Lin; Mengmeng Song; Xi Zhang; Xiaoyue Liu; Ming Yang; Meng Tang; et al. (Inflammation Research, 2022)

Isoflurane and Sevoflurane Induce Cognitive Impairment in Neonatal Rats by Inhibiting Neural Stem Cell Development Through Microglial Activation, Neuroinflammation, and Suppression of VEGFR2 Signaling Pathway - Chunlong Zuo; Junmei Ma; Yizhao Pan; Dongxu Zheng; Chunjiang Chen; Naqi Ruan; Ying Su; Haihan Nan; Qingquan Lian; Han Lin (Neurotoxicity Research, 2022)
Inhaled anesthetics are known to induce neurotoxicity in the developing brains of rodents, although the mechanisms are not well understood. The aim of this study was to elucidate the molecular mechanisms underlying anesthetics-induced neurodevelopmental toxicity by VEGF receptor 2 (VEGFR2) through the interaction between microglia and neural stem cells (NSCs) in postnatal day 7 (P7) rats. Cognitive function of P7 rats exposed to isoflurane and sevoflurane were assessed using Morris Water Maze and T maze tests. We also evaluated the expression levels of NSC biomarkers (Nestin and Sox2), microglia biomarker (CD11b or or IBA1), pro-inflammatory cytokines (IL-6 and TNF-α), and VEGFR2 using western blotting and immunohistochemistry in the brains of control and anesthesia-treated rats. We found spatial learning and working memory was impaired 2 weeks after anesthetics exposure in rats. Isoflurane induced stronger and more prolonged neurotoxicity than sevoflurane. However, cognitive functions were recovered 6 weeks after anesthesia. Isoflurane and sevoflurane decreased the levels of Nestin, Sox2, and p-VEGFR2, activated microglia, decreased the number of NSCs and reduced neurogenesis and the proliferation of NSCs, and increased the levels of IL-6, TNF-α, and CD11b. Our results suggested that isoflurane and sevoflurane induced cognitive impairment in rats by inhibiting NSC development and neurogenesis via microglial activation, neuroinflammation, and suppression of VEGFR2 signaling pathway.

Effects of local and non-local closure PBL schemes on the simulation of Super Typhoon Mangkhut (2018) - Zixi Ruan; Jiangnan Li; Fangzhou Li; Wenshi Lin (Frontiers of Earth Science, 2022)

Molecular Characterization of Aquaporins Genes from the Razor Clam Sinonovacula constricta and Their Potential Role in Salinity Tolerance - Wenbin Ruan; Yinghui Dong; Zhihua Lin; Lin He (Fishes, 2022)
Aquaporins (AQPs) play crucial roles in osmoregulation, but the knowledge about the functions of AQPs in Sinonovacula constricta is unclear. In this study, Sc-AQP1, Sc-AQP8, and Sc-AQP11 were identified from S. constricta, and the three Sc-AQPs are highly conserved compared to the known AQPs. The qRT-PCR analysis revealed that the highest mRNA expressions of Sc-AQP1, Sc-AQP8, and Sc-AQP11 were detected in the gill, digestive gland, and adductor muscle, respectively. In addition, the highest mRNA expression of Sc-AQP1 and Sc-AQP11 was detected in the D-shaped larvae stage, whereas that of SC-AQP8 was observed in the umbo larvae stage. The mRNA expression of Sc-AQP1, Sc-AQP8, and Sc-AQP11 significantly increased to 12.45-, 12.36-, and 27.44-folds post-exposure of low salinity (3.5 psu), while only Sc-AQP1 and Sc-AQP11 significantly increased post-exposure of high salinity (35 psu) (p

Environmental consequences of an ultra-low emission retrofit in coal-fired power plants from a life cycle perspective - Jun Dong; Yuanjun Tang; Aizhong Ruan; Jie Chen; Xiaoqing Lin; Shengyong Lu; Xiang Gao (Waste Disposal & Sustainable Energy, 2021)

Comparison of the elimination effectiveness of tetracycline and AmpC β-lactamase resistance genes in a municipal wastewater treatment plant using four parallel processes - Xiaojun Lin; Jingjing Ruan; Lu Huang; Jianbin Zhao; Yanbin Xu (Ecotoxicology, 2021)

Bioaccumulation and translocation of trace elements in soil-irrigation water-wheat in arid agricultural areas of Xin Jiang, China - Muyesaier Tudi; Huada Daniel Ruan; Yunjiang Yu; Li Wang; Binggan Wei; Shuangmei Tong; Chang Kong; Lin-sheng Yang (Ecotoxicology, 2021)

Phenolic constituents from the fresh pericarps of Juglans sigillata - Yi Lin; Jingjing Liang; Xiaogang Peng; Hanli Ruan (Natural Product Research, 2021)

Non-linear relationships and interactions of meteorological factors on mumps in Jinan, China - Shaoqian Lin; Shiman Ruan; Xingyi Geng; Kaijun Song; Liangliang Cui; Xiaoxue Liu; Yingjian Zhang; Meng Cao; Ying Zhang (International Journal of Biometeorology, 2021)

Alternation of soil bacterial and fungal communities by tomato–rice rotation in Hainan Island in Southeast of China - Xiang Ma; Minglun Du; Peng Liu; Yanqiong Tang; Hong Li; Qianhua Yuan; Yunze Ruan; Lei Meng; Jiachao Zhang; Min Lin; Zhu Liu (Archives of Microbiology, 2021)

Ecological and health risk assessment of trace elements in surface soil in an arid region of Xin Jiang, China - Muyesaier Tudi; Huada Daniel Ruan; Binggan Wei; Li Wang; Shuangmei Tong; Chang Kong; Lin-sheng Yang (Journal of Soils and Sediments, 2021)

Gentianella acuta prevents acute myocardial infarction induced by isoproterenol in rats via inhibition of galectin-3/TLR4/MyD88/NF-кB inflammatory signalling - Jia-Huan Sun; Hong-Xia Yang; Ting-Ting Yao; Yuan Li; Lin Ruan; Geng-Rui Xu; Chuang Zhang; Guo-Xin Guo; Ai-Ying Li (Inflammopharmacology, 2021)

Triterpenoids from the fresh pericarps of Juglans hopeiensis - Yi Lin; Xiaogang Peng; Juan Chen; Jia Zhou; Hanli Ruan (Natural Product Research, 2021)

Effects of MC-LR on histological structure and cell apoptosis in the kidney of grass carp (Ctenopharyngodon idella) - Li He; Lin Liu; Changgao Lin; Jiming Ruan; Ximei Liang; Ying Zhou; Lili Wei (Fish Physiology and Biochemistry, 2020)

Genetic basis of maize ear angle revealed by high-density single nucleotide polymorphism markers in four recombinant inbred line populations - Jingwei Lin; Shoukun Li; Gengyuan Liang; Meiling Liu; Taicheng Jin; Zhengwei Qu; Haoge Li; Shuisen Chen; Cong Li; Ao Zhang; Yanye Ruan; Zhenhai Cui (Euphytica, 2020)

An alternative splicing variant of mineralocorticoid receptor discovered in preeclampsia tissues and its effect on endothelial dysfunction - Mengxi Guo; Chengliang Zhou; Gufeng Xu; Lin Tang; Yechun Ruan; Ying Yu; Xianhua Lin; Dandan Wu; Hao Chen; Priscilla Yu; Luyang Jin; Yinyu Wang; et al. (Science China Life Sciences, 2020)

The Potential of Constructed Wetland Plants for Bioethanol Production - Yan Lin; Yafang Zhao; Xinyi Ruan; Tyler J. Barzee; Zhenyu Zhang; Hainan Kong; Xiaoling Zhang (BioEnergy Research, 2020)

MicroRNA-mediated responses to colchicine treatment in barley - Fang-Yao Sun; Lin Liu; Yi Yu; Xin-Ming Ruan; Cheng-Yu Wang; Qun-Wen Hu; De-Xiang Wu; Genlou Sun (Planta, 2020)

Intestinal and hepatic biotransformation of pyrrolizidine alkaloid N-oxides to toxic pyrrolizidine alkaloids - Mengbi Yang; Jiang Ma; Jianqing Ruan; Yang Ye; Peter Pi-Cheng Fu; Ge Lin (Archives of Toxicology, 2019)

QTL mapping for maize starch content and candidate gene prediction combined with co-expression network analysis - Feng Lin; Ling Zhou; Bing He; Xiaolin Zhang; Huixue Dai; Yiliang Qian; Long Ruan; Han Zhao (Theoretical and Applied Genetics, 2019)

Difference of trace element exposed routes and their health risks between agriculture and pastoral areas in Bay County Xinjiang, China - Muyesaier Tudi; Dung Tri Phung; Huada Daniel Ruan; Lin-sheng Yang; Hai-Jun Guo; Des Connell; Ross Sadler; Cordia Chu (Environmental Science and Pollution Research, 2019)

The analysis model of shaft resistance softening of a new type of static drill rooted super-long nodular pile - Wen-juan Yao; Wei Lu; Chen-yu Cai; Kun Lin Ruan (Arabian Journal of Geosciences, 2019)

Development and evaluation of a set of 135 EST-SNP markers in the transcriptome dataset of hard clam, Meretrix meretrix - Yinghui Dong; Yan Jing; Wenbin Ruan; Hanhan Yao; Lin He; Zhihua Lin (Conservation Genetics Resources, 2018)

Sensitivity of Cochliobolus heterostrophus to three demethylation inhibitor fungicides, propiconazole, diniconazole and prochloraz, and their efficacy against southern corn leaf blight in Fujian Province, China - Yuli Dai; Lin Gan; Hongchun Ruan; Niuniu Shi; Yixin Du; Lei Liao; Zhixia Wei; Zhenyong Teng; Furu Chen; Xiujuan Yang (European Journal of Plant Pathology, 2018)

CLDN6 enhances chemoresistance to ADM via AF-6/ERKs pathway in TNBC cell line MDAMB231 - Minlan Yang; Yanru Li; Yang Ruan; Yan Lu; Dongjing Lin; Yinping Xie; Bing Dong; Qihua Dang; Chengshi Quan (Molecular and Cellular Biochemistry, 2018)

Characterization of the complete mitochondrial genome sequence of the Asiatic toad Bufo gargarizans (Amphibia, Anura, Bufonidae) with phylogenetic analysis - Lichun Jiang; Min Zhang; Jie Liu; Lin Ma; Peng Yu; Qiping Ruan (Conservation Genetics Resources, 2018)

Induction of Rhesus Keratinocytes into Functional Ameloblasts by Mouse Embryonic Dental Mesenchyme - Ningsheng Ruan; Chensheng Lin; Xiuqing Dong; Xuefeng Hu; Yanding Zhang (Tissue Engineering and Regenerative Medicine, 2018)

Trichogramma parasitoids can distinguish between fertilized and unfertilized host eggs - Wen-Mei Du; Jing Xu; Yang-Yang Hou; Ying Lin; Lian-Sheng Zang; Xiangbing Yang; Jun-Jie Zhang; Chang-Chun Ruan; Nicolas Desneux (Journal of Pest Science, 2018)

Transcriptome profile analysis reveals cardiotoxicity of maduramicin in primary chicken myocardial cells - Xiuge Gao; Lin Peng; Xiangchun Ruan; Xin Chen; Hui Ji; Junxiao Ma; Han Ni; Shanxiang Jiang; Dawei Guo (Archives of Toxicology, 2018)

Effect of low-molecular-weight organic acids on hematite dissolution promoted by desferrioxamine B - Qingqi Lin; Yingli Wang; Xiuhong Yang; Dishen Ruan; Shizhong Wang; Xiange Wei; Rongliang Qiu (Environmental Science and Pollution Research, 2018)

Foxo1 Attenuates NaF-Induced Apoptosis of LS8 Cells through the JNK and Mitochondrial Pathways - Juedan Li; Lin Zhao; Xiaomeng Zhao; Peng Wang; Yan Liu; Jianping Ruan (Biological Trace Element Research, 2018)

First evidence of pyrrolizidine alkaloid N-oxide-induced hepatic sinusoidal obstruction syndrome in humans - Mengbi Yang; Jianqing Ruan; Hong Gao; Na Li; Jiang Ma; Junyi Xue; Yang Ye; Peter Pi-Cheng Fu; Jiyao Wang; Ge Lin (Archives of Toxicology, 2017)

A novel beta-galactose-specific lectin of the tubeworm, Ridgeia piscesae, from the hydrothermal vent - Lingwei Ruan; Haipeng Xu; Wenyang Lin; Hong Shi; Zhizhong Cui; Xun Xu (Acta Oceanologica Sinica, 2017)

EGFL7-overexpressing epidermal stem cells promotes fibroblast proliferation and migration via mediating cell adhesion and strengthening cytoskeleton - Rong-Hua Yang; Shao-Hai Qi; Shu-Bin Ruan; Ze-Peng Lin; Yan Lin; Feng-Gang Zhang; Xiao-Dong Chen; Ju-Lin Xie (Molecular and Cellular Biochemistry, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

Tectonic evolution of Tarim basin in Cambrian–Ordovician and its implication for reservoir development, NW China - Yu BINGSONG; RUAN ZHUANG; ZHANG CONG; PAN YINGLU; LIN CHANGSONG; WANG LIDONG (Journal of Earth System Science, 2016)

Diversity and dynamics of bacteriocins from human microbiome - Jinshui Zheng; Michael G. Gänzle; Xiaoxi B. Lin; Lifang Ruan; Ming Sun (Environmental Microbiology, 2015)
Summary Human commensal microbiota are an important determinant of health and disease of the host. Different human body sites harbour different bacterial microbiota, bacterial communities that maintain a stable balance. However, many of the factors influencing the stabilities of bacterial communities associated with humans remain unknown. In this study, we identified putative bacteriocins produced by human commensal microbiota. Bacteriocins are peptides or proteins with antimicrobial activity that contribute to the stability and dynamics of microbial communities. We employed bioinformatic analyses to identify putative bacteriocin sequences in metagenomic sequences obtained from different human body sites. Prevailing bacterial taxa of the putative bacteriocins producers matched the most abundant organisms in each human body site. Remarkably, we found that samples from different body sites contain different density of putative bacteriocin genes, with the highest in samples from the vagina, the airway, and the oral cavity and the lowest in those from gut. Inherent differences of different body sites thus influence the density and types of bacteriocins produced by commensal bacteria. Our results suggest that bacteriocins play important roles to allow different bacteria to occupy several human body sites, and to establish a long‐term commensal relationship with human hosts.

Antidepressant-like effects of ferulic acid: involvement of serotonergic and norepinergic systems - Jianliang Chen; Dan Lin; Chong Zhang; Gaowen Li; Nianping Zhang; Lina Ruan; Qizhi Yan; Jianxin Li; Xuefeng Yu; Xupei Xie; Cong Pang; Liang Cao; et al. (Metabolic Brain Disease, 2015)

The study of regulatory effects of Pdx-1, MafA and NeuroD1 on the activity of porcine insulin promoter and the expression of human islet amyloid polypeptide - Xiao-Dan Liu; Jin-Xue Ruan; Ji-Han Xia; Shu-Lin Yang; Jun-Hua Fan; Kui Li (Molecular and Cellular Biochemistry, 2014)

Structural basis for RKIP binding with its substrate Raf1 kinase - Zhihua Wu; Cuiping Fu; Lina Shi; Lu Ruan; Donghai Lin; Chenyun Guo (Biotechnology Letters, 2014)

Epigenetic control of Pollen Ole e 1 allergen and extensin family gene expression in Arabidopsis thaliana - Bo Hu; Boyu Liu; Ling Liu; Chunlin Liu; Lin Xu; Ying Ruan (Acta Physiologiae Plantarum, 2014)

Ferulic acid increases pain threshold and ameliorates depression-like behaviors in reserpine-treated mice: behavioral and neurobiological analyses - Ying Xu; Lu Zhang; Tuo Shao; Lina Ruan; Lin Wang; Jiao Sun; Jianxin Li; Xinbo Zhu; James M. O’Donnell; Jianchun Pan (Metabolic Brain Disease, 2013)

Requests for Health Education from Chinese Cancer Patients During Their Recovery Period: a Cross-Sectional Study - Wei-Li Qiu; Pei-Juan Lin; Fei-Qun Ruan; Xiao Wu; Miao-Ping Lin; Lian Liu; Jia-Yi Luo; Kun Lin (Journal of Cancer Education, 2013)

Halomonas socia sp. nov., isolated from high salt culture of Dunaliella salina - Jiao Cao; Huai-Yuan Ma; Hai-Yu Li; Kui-Rong Wang; Kun Ruan; Lin-Han Bai (Extremophiles, 2013)

Overlapping transcription structure of human cytomegalovirus UL140 and UL141 genes - Yanping Ma; Mali Li; Bo Zheng; Ning Wang; Shuang Gao; Lin Wang; Ying Qi; Zhengrong Sun; Qiang Ruan (Journal of Biosciences, 2013)

Transcription characteristics of the human cytomegalovirus UL13 gene - Ning Wang; Yanping Ma; Mali Li; Shuang Gao; Lin Wang; Ying Qi; Yaohua Ji; Zhengrong Sun; Qiang Ruan (Archives of Virology, 2013)

Conservation and characterization of unique porcine interstitial telomeric sequences - GuangZhen Ji; Kai Liu; ChengBin Chen; WeiMin Ruan; Christina Glytsou; Yang Yang; Maja Okuka; WenQing Song; Sarantis Gagos; Ning Li; Lin Liu (Science China Life Sciences, 2012)

Nkx2-1: a novel tumor biomarker of lung cancer - Li Yang; Min Lin; Wen-jing Ruan; Liang-liang Dong; En-guo Chen; Xiao-hong Wu; Ke-jing Ying (Journal of Zhejiang University-SCIENCE B, 2012)

The Response of Soil Nematode Community to Nitrogen, Water, and Grazing History in the Inner Mongolian Steppe, China - Wei-bin Ruan; Yuan Sang; Qing Chen; Xiang Zhu; Shan Lin; Yu-bao Gao (Ecosystems, 2012)

Structural and functional conservation of CLEC-2 with the species-specific regulation of transcript expression in evolution - Lan Wang; Shifang Ren; Haiyan Zhu; Dongmei Zhang; Yuqing Hao; Yuanyuan Ruan; Lei Zhou; Chiayu Lee; Lin Qiu; Xiaojing Yun; Jianhui Xie (Glycoconjugate Journal, 2012)

Effect of the C-terminal domains and terminal residues of catalytic domain on enzymatic activity and thermostability of lichenase from Clostridium thermocellum - Dong Niu; Xu-xia Zhou; Tao-yan Yuan; Zhi-wei Lin; Hui Ruan; Wei-fen Li (Biotechnology Letters, 2010)

A novel triple-regulated oncolytic adenovirus carrying PDCD5 gene exerts potent antitumor efficacy on common human leukemic cell lines - Min Xie; Ji-Hong Niu; Yan Chang; Qi-Jun Qian; Hong-Ping Wu; Lin-Fang Li; Yao Zhang; Jin-Lan Li; Xiao-Jun Huang; Guo-Rui Ruan (Apoptosis, 2009)

Takayasu’s arteritis associated with Crohn’s disease - You-shi Liu; You-hong Fang; Ling-xiang Ruan; You-ming Li; Lin Li; Ling-ling Jiang (Journal of Zhejiang University-SCIENCE B, 2009)

Genetic similarity among cultivars of Phyllostachys pubescens - Xin Chun Lin; Xiao Sai Ruan; Yong Feng Lou; Xiao Qin Guo; Wei Fang (Plant Systematics and Evolution, 2009)

Cloning and expression study of a putative carotene biosynthesis related (cbr) gene from the halotolerant green alga Dunaliella salina - Chen Chen; Lin Han Bai; Dai Rong Qiao; Hui Xu; Gui Ling Dong; Kun Ruan; Fei Huang; Yi Cao (Molecular Biology Reports, 2008)

IGFBP7 plays a potential tumor suppressor role against colorectal carcinogenesis with its expression associated with DNA hypomethylation of exon 1 - Wen-jing Ruan; Jie Lin; En-ping Xu; Fang-ying Xu; Yu Ma; Hong Deng; Qiong Huang; Bing-jian Lv; Hu Hu; Jing Cui; Mei-juan Di; Jian-kang Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2006)

A novel dual peroxisome proliferator-activated receptors α and γ agonist with beneficial effects on insulin resistance and lipid metabolism - Cheng Xu; Li-Li Wang; Hong-Ying Liu; Cheng-Mai Ruan; Xing-Bo Zhou; Ying-Lin Cao; Song Li (Biotechnology Letters, 2006)